Hox Proteins Display a Common and Ancestral Ability to Diversify Their Interaction Mode with the PBC Class Cofactors. - Hudry, B.; Remacle, S.; Delfini, M.C.; Rezsohazy, R.; Graba, Y.; Merabet, S. (PLoS Biology, 2012)
Hox transcription factors control a number of developmental processes with the help of the PBC class proteins. In vitro analyses have established that the formation of Hox/PBC complexes relies on a short conserved Hox protein motif called the hexapeptide (HX). This paradigm is at the basis of the vast majority of experimental approaches dedicated to the study of Hox protein function. Here we questioned the unique and general use of the HX for PBC recruitment by using the Bimolecular Fluorescence Complementation (BiFC) assay. This method allows analyzing Hox-PBC interactions in vivo and at a genome-wide scale. We found that the HX is dispensable for PBC recruitment in the majority of investigated Drosophila and mouse Hox proteins. We showed that HX-independent interaction modes are uncovered by the presence of Meis class cofactors, a property which was also observed with Hox proteins of the cnidarian sea anemone Nematostella vectensis. Finally, we revealed that paralog-specific motifs convey major PBC-recruiting functions in Drosophila Hox proteins. Altogether, our results highlight that flexibility in Hox-PBC interactions is an ancestral and evolutionary conserved character, which has strong implications for the understanding of Hox protein functions during normal development and pathologic processes.